10=(n-6)/9

Simple and best practice solution for 10=(n-6)/9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10=(n-6)/9 equation:


n in (-oo:+oo)

10 = (n-6)/9 // - (n-6)/9

10-((n-6)/9) = 0

(-1*(n-6))/9+10 = 0

(-1*(n-6))/9+(9*10)/9 = 0

9*10-1*(n-6) = 0

96-n = 0

(96-n)/9 = 0

(96-n)/9 = 0 // * 9

96-n = 0

96-n = 0 // - 96

-n = -96 // * -1

n = 96

n = 96

See similar equations:

| -5/10-3/10 | | x=p^4-6p^3+300 | | 1/3*5*8 | | 2.6x=15 | | 15x^2-4x=3 | | 5=2k+10 | | 560-13n=365 | | x+y=8.99 | | 3(x+7)=5(x+5) | | xy=8.99 | | 48=2w^2+4w | | (36x^7y^6)1/2 | | 48=2w+4w | | 16s^2-137s-63= | | r(z^9-7)-(z^9-7)= | | Y=1-(6) | | 3(0)-2y+2(-2)=-2 | | 2k+3(k-4)=-3 | | 7z+5=7 | | Y=1-(9) | | 25m^2=36 | | 2a^2=12a^2 | | h(t)=-16t^2+32t+24 | | 1/4-1/2/1/5-1/3 | | 10x+4(-2)=-8 | | 4=(4w)/1 | | y(x+2)-4(x+2)= | | 4+7(x-2)=9-9(x-7) | | 9b-2+74=180 | | 2x-1y=8.99 | | 8x^5+16x^7-20x^4+28= | | 9n-n= |

Equations solver categories